Prognostic but not predictive role of platelet-derived growth factor receptors in patients with recurrent glioblastoma - Paulsson, Janna; Lindh, Maja Bradic; Jarvius, Malin; Puputti, Marjut; Nistér, Monica; Nupponen, Nina N.; Paulus, Werner; Söderberg, Ola; Dresemann, Gregor; Deimling, Andreas von; Joensuu, Heikki; Ostman, Arne; et al. (International journal of cancer, 2011)
Platelet-derived growth factor receptor (PDGFR) signaling has been implicated in the pathogenesis of glioblastomas and represents a target for the tyrosine kinase inhibitor imatinib. To examine the prognostic or predictive role of PDGFRs in recurrent glioblastomas, expression was examined in tumor samples of 101 patients of CSTI571BDE40, a randomized trial comparing hydroxyurea monotherapy and a combination of hydroxyurea and imatinib. Furthermore, PDGFRα phosphorylation was investigated using in situ proximity ligation assay. PDGFRα protein was expressed in 33% of tumors and was associated with male sex, young age, presence of R132H mutated isocitrate dehydrogenase 1 protein and short median survival (142 vs. 187 days, p = 0.028). Tumor PDGFRα phosphorylation was also associated with short survival (p = 0.030). The subset of patients with PDGFRα positive glioblastoma did not have longer survival on treatment with hydroxyurea and imatinib compared with hydroxyurea monotherapy. In conclusion, both PDGFRα protein expression and phosphorylation status had a prognostic role in recurrent glioblastomas but did not define a group that showed benefit from the combination therapy consisting of hydroxyurea and imatinib.
Gesehen am 29.09.2022